2005
DOI: 10.1080/02652030400029439
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of duplicate 24-hour diet samples for aflatoxin B1, aflatoxin M1and ochratoxin A

Abstract: In the spring and autumn of 1994, a total diet study, in which 123 participants collected duplicates of their 24-hour diets, was carried out. The goal of this study was to determine the mass fractions of a number of analytes in these duplicate diets, so as to be able to establish oral daily intake values. After measurements were carried out for pesticides, PCBs, elements, sterols, nitrate and nitrite, and fatty acids, the duplicate diet study was concluded with analyses for aflatoxin M1, aflatoxin B1 and ochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 7 publications
2
34
3
Order By: Relevance
“…Information on gender, age and body weight of the participants was collected. The design and sampling procedure were the same as applied in an earlier duplicate diet study that was performed in 1994 by RIVM and described by Sizoo and van Egmond (2005). Duplicate 24-h food and drink portions, including drinking water, were collected during the two study periods each to take seasonal fluctuations in food composition and consumption into account.…”
Section: Methodsmentioning
confidence: 99%
“…Information on gender, age and body weight of the participants was collected. The design and sampling procedure were the same as applied in an earlier duplicate diet study that was performed in 1994 by RIVM and described by Sizoo and van Egmond (2005). Duplicate 24-h food and drink portions, including drinking water, were collected during the two study periods each to take seasonal fluctuations in food composition and consumption into account.…”
Section: Methodsmentioning
confidence: 99%
“…Total mycotoxin (aflatoxin B 1 [AFB 1 ] and OTA) contents of eggs was determined by HPLC (Sizoo and van Egmond 2005). For this purpose, a total of ninety eggs were selected and twenty pooled samples, each composed of five blended eggs, were prepared.…”
Section: Experimental Designmentioning
confidence: 99%
“…A duplicate diet study in adults performed in 1994 reported an average exposure of < 0.03 ng/kg bw per day for aflatoxin B 1 (N=123; Sizoo and Van Egmond, 2004), while a similar study carried out in 2004 showed a somewhat higher (median) exposure of 0.04 ng/kg bw per day (N=61; Van Egmond, 2006). As the variation was relatively high (e.g.…”
Section: Trends In Exposurementioning
confidence: 99%